Penyuluhan Tentang Program Posyandu Pada Ibu-Ibu Kader Di Desa Wonorejo Kecamatan Poncokusumo - Rokhamah, Rokhamah; Yusnita, Yusnita; Emi, Emi (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2024)
Service post is a health effort managed by, from, for and with the community in order to empower and provide convenience in maternal, infant, and toddler health services Health cadres are the spearhead of the implementation of Posyandu in the community. There are still many cadres who do not understand in detail about the posyandu program. The purpose of this community service is to provide education about posyandu and its programs so that cadres will understand better so that they are finally able to play an active role in the implementation of posyandu activities. The method used in this counseling uses lecture-based counseling methods as a technique. A lecture format is used to introduce the topics in this exercise, followed by guided practice and assessment. The results obtained after this counseling activity increased the cadres' understanding of posyandu and its programs, this was shown by the evaluation process when the cadres were able to answer questions from the extension team.